Mobile Learning for Early Detection of Cancer - Muljo, Hery Harjono; Perbangsa, Anzaludin Samsinga; Yulius, Yulius; Pardamean, Bens (International Journal of Interactive Mobile Technologies (iJIM), 2018)
Information and communication technology continues to grow and affects many areas of life, including the field of health, especially cancer. The development of health knowledge can be disseminated by utilizing mobile application based learning technology as media. Many things have been done by the government through special programs, among others, carried out breast cancer awareness campaign through breast self-screening program. The positive impact of this effort has led to mobile applications for learning about early detection of cancer in Indonesia. The development of mobile learning is a continuation of previous online learning to help the process of early detection of cervical cancer. Data collection methods used observation, interview, and questionnaire techniques, while instructional designs use the ADDIE (Analysis Design Development Implementation Evaluations) model and methods for developing object-oriented programming systems using Unified Modeling Language (UML). The resulting output is the application of early detection of cancer-based mobile learning which is the virtue of this study.